Baza danych REGIO jako źródło informacji o turystyce w regionach Unii Europejskiej - Obrębalski, Marek (REGIO Database as a Source of Information About Tourism in the EU Regions, 2005)
The Statistical Office of European Community (Eurostat) leads regional database (REGIO). The data in REGIO are all broken down by territorial units, using the Nomenclature of Territorial Units for Statistics (NUTS). REGIO is a database specifically dedicated to statistics on economic life in each Member State of the European Union. There are sixteen collections in REGIO. The data in REGIO cover a wide range of subjects. It refers also to information about tourism. The collection on regional tourism statistics contains data on the capacity of collective tourist accommodation (number of establishments, number of bedrooms, number of bedplaces) and occupancy in collective accommodation establishments (arrivals and nights spent, broken down into residents and non-residents). Tourist accommodation in Europe has a few concentration places in touristical regions, especially in northern and central Italy, southern France and southern Spain. The real information on tourism in regional profile are very useful in the application of international comparative analysis.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1074, s. 264-272